2014
DOI: 10.1177/1758573214528155
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting short- and long-term outcomes of manipulation under anaesthesia in patients with adhesive capsulitis of the shoulder

Abstract: Background: The present study aimed to evaluate and determine the factors that affect short-and long-term outcome following manipulation under anaesthesia (MUA) of patients with adhesive capsulitis. Methods: Patients recruited from January 1999 to January 2010 were retrospectively analyzed and classified as having primary or secondary adhesive capsulitis. All patients were assessed for range of movement (ROM) and Oxford Shoulder Scores (OSS) before and immediately postoperatively, as well as for OSS more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…However, in our study, diabetic patients showed slightly worse outcomes compared with non-diabetic patients although outcome variables in the ACR group were not significantly different. We observed no differences in any outcome variables in the MUA group, a finding that is consistent with those of other reports and suggests that diabetes is not a contraindication for MUA [16,18,31,34]. Regarding recurrence after surgery, Jenkins et al reported that re-…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in our study, diabetic patients showed slightly worse outcomes compared with non-diabetic patients although outcome variables in the ACR group were not significantly different. We observed no differences in any outcome variables in the MUA group, a finding that is consistent with those of other reports and suggests that diabetes is not a contraindication for MUA [16,18,31,34]. Regarding recurrence after surgery, Jenkins et al reported that re-…”
Section: Discussionsupporting
confidence: 92%
“…FS is strongly associated with diabetes and is two to four times more common in diabetic patients than in the general population [32][33][34][35][36]. FS in patients with diabetes tends to have a more severe and protracted course, and to be difficult to treat [32,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate after MUA varies from 3% to 40% 585960). Jenkins et al59) reported that 36% of patients who had diabetic FS required a repeat MUA versus 15% for nondiabetic shoulders.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Despite our short follow-up time, we have previously presented work showing that OSS is maintained in the longer term for patients following MUA. 7,16 We have also shown that patients usually respond to MUA within a very short time frame, usually within a few days, and certainly within 3 weeks, such that, if no or minimal improvement is shown at followup, then further progress is unlikely. However, we attempt further non-operative treatment in these patients unless (or until) they make no further progress and therefore the offer of a repeat MUA at this stage is justified.…”
Section: Discussionmentioning
confidence: 93%
“…Despite our short follow-up time, we have previously presented work showing that OSS is maintained in the longer term for patients following MUA. 7,16…”
Section: Discussionmentioning
confidence: 99%